Morphologic changes in the vesical transition epithelium of alcoholic rats - Mello, W.; Garcia, P. J.; Cagnon, VHA; Martinez, M.; Martinez, F. E. (Editrice Compositori Bologna, 1997)
Few studies are available about the effect of alcohol on the epithelium of the urinary bladder. In the present investigation we studied the ultrastructure of the vesical transition epithelium of normal rats and of rats submitted to experimental chronic alcoholism. Adult rats were submitted to experimental chronic alcoholism by the ingestion of sugar cane liquor. The vesical epithelium was examined after 60, 120, 180 and 240 days of alcohol treatment by transmission electron microscopy. Surface cells presented nuclear and cytoplasmic changes and marked cellular desquamation. There was an increase in multivesicular bodies and lysosomes suggesting cell degeneration. Mast cell infiltration was observed, possibly related to increased epithelial sensitivity. Intercellular spaces were frequently observed. The transition epithelium of the urinary bladder was found to be sensitive to the action of alcohol, as demonstrated by the changes in the components of the blood-urine barrier, the greater sensitivity to inflammation, the increase in cell desquamation and the greater recycling of the apical membrane and of the fusiform vesicles of surface cells observed in alcoholic rats.
Keywords: epithelium urinary bladder; alcoholism; rat; electron microscopy